Pharmacokinetics and Pharmacokinetic/Pharmacodynamic Integration of Enrofloxacin Following Single Oral Administration of Different Doses in Brown Trout (Salmo trutta) - Kamil Uney; Ertugrul Terzi; Duygu Durna Corum; Rahmi Can Ozdemir; Soner Bilen; Orhan Corum (Animals, 2021)
The pharmacokinetic of enrofloxacin was investigated in brown trout (Salmo trutta) following oral administration of 10, 20, and 40 mg/kg doses at 11 ± 1.5 °C. Furthermore, MICs of enrofloxacin against Aeromonas hydrophila and A. sobria were determined. The plasma concentrations of enrofloxacin and ciprofloxacin were determined using HPLC–UV and analyzed by non-compartmental method. Following oral administration at dose of 10 mg/kg, total clearance (CL/F), area under the concentration–time curve (AUC0−∞) and peak plasma concentrations (Cmax) were 41.32 mL/h/kg, 242.02 h*μg/mL and 4.63 μg/mL, respectively. When compared to 10 mg/kg dose, the dose-normalized AUC0–∞ and Cmax were increased by 56.30% and 30.08%, respectively, while CL/F decreased by 38.4% at 40 mg/kg dose, suggesting the non-linearity. Ciprofloxacin was not detected in the all of plasma samples. The MIC values of enrofloxacin were ranged 0.0625–4 μg/mL for A. hydrophila and 0.0625–2 μg/mL for A. sobria. The oral administration of enrofloxacin at 10 (for 192 h) and 20 (for 240 h) mg/kg doses provided the AUC of enrofloxacin equal to 1.23 and 1.96-fold MICs, respectively, for A. hydrophila and A. sobria with the MIC90 values of 1 µg/mL. However, further researches are needed on the PK/PD study of enrofloxacin for the successful treatment of infections caused by A. hydrophila and A. sobria in brown trout.